Ultra-high performance concrete as well as preparation method and application thereof

By using porous ceramic sand and ceramic sand aggregates of different particle sizes in ultra-high performance concrete, combined with silica fume and stone powder, the problems of existing ultra-high performance concrete in impact resistance and shrinkage deformation are solved, and higher impact resistance and lower shrinkage deformation are achieved, extending the service cycle of the building.

CN119841593APending Publication Date: 2025-04-18CHINA STATE CONSTR HAILONG TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411854622.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing ultra-high performance concrete still has room for improvement in impact resistance. Moreover, due to the large amount of gelling materials and the low water-gluing ratio, it is easy to cause the concrete to shrink and deform and cracks to occur.

Method used

Porous ceramic sand is used as aggregate, and good grades are formed by combining ceramic sand with different particle size ranges (≤0.6mm, 0.6-1.25mm, 1.25-2.36mm and 2.36-4.75mm) and an appropriate amount of silica fume and stone powder to form a good grading, reducing void ratio, improving density and impact resistance.

Benefits of technology

It significantly improves the impact resistance of ultra-high performance concrete, reduces the shrinkage deformation of concrete, extends the service cycle, and improves the compressive strength and durability of the building.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841593A_ABST
    Figure CN119841593A_ABST
Patent Text Reader

Abstract

The invention relates to ultra-high performance concrete and a preparation method and application thereof, and the ultra-high performance concrete comprises the following components in parts by weight: 700-800 parts of cement, 150-160 parts of silica fume, 210-220 parts of stone powder and 844 parts of pottery sand. Wherein 101-272 parts of the pottery sand with the particle size smaller than or equal to 0.6 mm, 266-345 parts of the pottery sand with the particle size ranging from 0.6 mm to 1.25 mm, 76-306 parts of the pottery sand with the particle size ranging from 1.25 mm to 2.36 mm and 0-322 parts of the pottery sand with the particle size ranging from 2.36 mm to 4.75 mm are included. The ultra-high performance concrete has the beneficial effects that the shrinkage of the ultra-high performance concrete can be obviously reduced and the impact resistance of the ultra-high performance concrete can be obviously improved while the compressive strength is ensured, the ultra-high performance concrete can be suitable for buildings with relatively high requirements on impact resistance, and the building performance of the ultra-high performance concrete is comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to an ultra-high performance concrete and a preparation method and application thereof. Background Art

[0002] Ultra-High Performance Concrete (UHPC) is a new type of cement-based composite material with excellent mechanical properties, durability and toughness, and can be used under various special service conditions.

[0003] In order to achieve the above-mentioned excellent performance, the existing ultra-high performance concrete usually uses finer aggregates to achieve the effect of dense packing, which also makes the ultra-high performance concrete heavy, bringing difficulties to the design and construction of the mechanism. Although the replacement of lightweight aggregates can reduce the weight to a certain extent, it will also affect the strength of ultra-high performance concrete. At the same time, due to the large amount of cementitious materials and low water-cement ratio in this system, it is easy to cause large shrinkage deformation of concrete and cracks. In addition, in order to improve the impact resistance of UHPC, the patent document with publication number CN113683361A uses fine aggregate (particle size ≤ 1.25mm) as aggregate, and replaces part of the river sand in the fine aggregate with ecological porous ceramic sand. The energy required for the first crack of the UHPC prepared in the impact resistance test is 1131.9J. Although the impact resistance is improved to a certain extent, it still cannot meet the use in application scenarios where large impact forces are repeatedly generated. The impact resistance of UHPC still has room for improvement. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides an ultra-high performance concrete and a preparation method and application thereof, which solves the technical problem that the comprehensive performance of the existing ultra-high performance concrete needs to be improved.

[0006] (II) Technical solution

[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0008] In a first aspect, an embodiment of the present invention provides an ultra-high performance concrete, comprising, by weight: 700-800 parts of cement, 150-160 parts of silica fume, 210-220 parts of stone powder and 844 parts of pottery sand; wherein, 101-272 parts of pottery sand with a particle size ≤0.6 mm, 266-345 parts of pottery sand with a particle size of 0.6-1.25 mm, 76-306 parts of pottery sand with a particle size of 1.25-2.36 mm, and 0-322 parts of pottery sand with a particle size of 2.36-4.75 mm.

[0009] The pottery sand used here is a porous aggregate made from sludge, with low density and porous structure, and an average porosity of 20% to 30%. The pore structure can store and retain water. As the cement hydration consumes water, the internal relative humidity of the local cement slurry decreases. At this time, the water stored in the pore structure of the pottery sand is released again, so that the capillary pores inside the concrete remain saturated, thereby reducing the shrinkage of the concrete, avoiding cracks in the UHPC, and effectively extending the service life of the UHPC. The raw materials for preparing pottery sand are relatively abundant, realizing the recycling of resources.

[0010] In addition, the porous structure of ceramic sand leads to a high specific surface area, and the low density can also reduce the weight of concrete, making it easier to transport and construct. Most importantly, the use of ceramic sand aggregate with continuous particle size and larger particle size can effectively absorb and store energy, significantly improving the impact resistance of ultra-high performance concrete.

[0011] The technical bias of the prior art that finer aggregates are usually used to achieve dense packing is overcome. The above four particle size ranges of ceramic sand are selected with corresponding mass fractions. In this way, even if larger particle size aggregates are introduced compared to the prior art, a good dense packing effect can be achieved to meet the strength requirements of ultra-high performance concrete.

[0012] As a preferred embodiment of the present invention, the ultra-high performance concrete includes, by weight: 770 parts of cement, 150 parts of silica fume, 210 parts of stone powder and 844 parts of pottery sand; among them, 270-272 parts of pottery sand with a particle size of ≤0.6 mm, 266-268 parts of pottery sand with a particle size of 0.6-1.25 mm, and 304-306 parts of pottery sand with a particle size of 1.25-2.36 mm.

[0013] As a preferred embodiment of the present invention, the ultra-high performance concrete includes, by weight: 770 parts of cement, 150 parts of silica fume, 210 parts of stone powder and 844 parts of pottery sand; among them, 101-103 parts of pottery sand with a particle size of ≤0.6 mm, 343-345 parts of pottery sand with a particle size of 0.6-1.25 mm, 76-78 parts of pottery sand with a particle size of 1.25-2.36 mm, and 320-322 parts of pottery sand with a particle size of 2.36-4.75 mm.

[0014] Using ceramic sand as aggregate in the above four particle size ranges and matching the corresponding mass fractions can achieve the best dense packing effect, and the prepared ultra-high performance concrete has the best comprehensive performance.

[0015] As a preferred embodiment of the present invention, the ultra-high performance concrete further comprises, by weight: 35-37 parts of polycarboxylate water-reducing agent and 200-220 parts of water.

[0016] As a preferred embodiment of the present invention, the ultra-high performance concrete comprises 35 parts of polycarboxylate water-reducing agent and 200 parts of water.

[0017] In a second aspect, an embodiment of the present invention provides a method for preparing the ultra-high performance concrete according to the first aspect, comprising the following steps:

[0018] S1, first mix cement, silica fume and stone powder, then add pottery sand and mix well to obtain a mixed dry material;

[0019] S2, adding the mixed water and water reducing agent to the mixed dry materials, stirring to form a slurry;

[0020] S3, putting the slurry into a mold for shaping and curing to obtain the ultra-high performance concrete.

[0021] As a preferred embodiment of the present invention, in the preparation method, in S1, the stirring speed during the mixing process is 30-60 rpm, wherein the cement, silica fume and stone powder are mixed for 30-40 seconds;

[0022] The ceramic sand is added within 15 seconds, and then stirring is continued for 45-60 seconds to obtain a mixed dry material.

[0023] As a preferred embodiment of the present invention, in the preparation method, in S2, the stirring speed is 30-60rpm, and after the mixed dry materials, water and water reducer are stirred to form a uniform slurry, the stirring is continued for 180s to ensure that the slurry and aggregate are fully mixed and uniform to obtain the slurry.

[0024] In a third aspect, an embodiment of the present invention provides a use of the ultra-high performance concrete described in the first aspect, which is used for buildings in earthquake-prone areas, offshore platform buildings, bridges and dams of water conservancy projects, and explosion-proof buildings.

[0025] Ultra-high performance concrete is used in the above building structures with relatively high requirements for impact resistance, which can effectively improve the impact resistance of the building and extend the service life of the building structure.

[0026] (III) Beneficial effects

[0027] The beneficial effects of the present invention are as follows: the ultra-high performance concrete and its preparation method and application of the present invention, because pottery sand is used as both coarse aggregate and fine aggregate, overcomes the technical bias of the prior art that finer aggregate is usually used to achieve the dense packing effect. And pottery sand with four particle sizes of ≤0.6mm, 0.6-1.25mm, 1.25-2.36mm and 2.36-4.75mm is combined and mixed, and the amount of pottery sand in different particle size ranges is matched, the pottery sand can form a good gradation, reduce the void ratio, help to improve the density and strength of UHPC, and also reduce the shrinkage of UHPC. The addition of silica fume and stone powder can improve the density and durability of UHPC, and silica fume can also increase the strength and impermeability of UHPC. Compared with the prior art, it can significantly reduce the shrinkage of ultra-high performance concrete while ensuring the compressive strength, significantly improve the impact resistance of ultra-high performance concrete, can be applied to buildings with high requirements for impact resistance, and comprehensively improve the construction performance of ultra-high performance concrete.

[0028] The composition of the ceramic sand is: 270-272 parts of ceramic sand with a particle size of ≤0.6mm, 266-268 parts of ceramic sand with a particle size of 0.6-1.25mm, and 304-306 parts of ceramic sand with a particle size of 1.25-2.36mm; or, 101-103 parts of ceramic sand with a particle size of ≤0.6mm, 343-345 parts of ceramic sand with a particle size of 0.6-1.25mm, 76-78 parts of ceramic sand with a particle size of 1.25-2.36mm, and 320-322 parts of ceramic sand with a particle size of 2.36-4.75mm; the ceramic sand forms a good gradation relationship, and the comprehensive construction performance of the ultra-high performance concrete is significantly improved. The energy required to produce the first crack in the impact resistance test is as high as 7060.37J, and the impact resistance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A comparison chart of the compressive strength of UHPC prepared in different embodiments and comparative examples at different ages;

[0030] Figure 2 It is a comparison chart of the shrinkage performance of UHPC prepared in different embodiments and comparative examples;

[0031] Figure 3 It is a comparison chart of the impact resistance of UHPC prepared in different embodiments and comparative examples. DETAILED DESCRIPTION

[0032] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0033] The ultra-high performance concrete and its preparation method and application proposed in the embodiment of the present invention aim at the technical problem that the comprehensive performance of the existing ultra-high performance concrete needs to be improved. Since pottery sand is used as both coarse aggregate and fine aggregate, the technical bias of the prior art that finer aggregates are usually used to achieve the dense packing effect is overcome. In addition, pottery sands with four particle sizes of ≤0.6mm, 0.6-1.25mm, 1.25-2.36mm and 2.36-4.75mm are combined and mixed, and the amount of pottery sands in different particle size ranges is matched. The pottery sands can form a good gradation, reduce the porosity, help improve the density and strength of UHPC, and also reduce the shrinkage of UHPC. The addition of silica fume and stone powder can improve the density and durability of UHPC, and the silica fume can also increase the strength and impermeability of UHPC. Compared with the existing technology, it can significantly reduce the shrinkage of ultra-high performance concrete while ensuring the compressive strength, significantly improve the impact resistance of ultra-high performance concrete, and can be used in buildings with high requirements for impact resistance, thereby comprehensively improving the construction performance of ultra-high performance concrete.

[0034] In order to better understand the above technical solution, exemplary embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a clearer and more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.

[0035] Example 1

[0036] This embodiment provides a method for preparing ultra-high performance concrete, comprising the following steps:

[0037] (1) According to the weight percentage, 770 parts of P·O52.5 ordinary Portland cement, 150 parts of silica fume and 210 parts of stone powder were added to a stirring pot and stirred at a speed of 30 rpm for 30 seconds. Then, 844 parts of pottery sand were added to the stirring pot within 15 seconds, and the mixture was slowly stirred at a speed of 30 rpm for 45 seconds to obtain a mixed dry material;

[0038] Among them, 844 parts of pottery sand include 272 parts of pottery sand with a particle size of ≤0.6mm, 266 parts of pottery sand with a particle size of 0.6-1.25mm, and 306 parts of pottery sand with a particle size of 1.25-2.36mm;

[0039] (2) adding 200 parts of water and 35 parts of water reducing agent to the mixed dry materials, stirring at a speed of 30 rpm to form a slurry, and then continuing to stir slowly for 180 seconds to form a slurry for standby use;

[0040] The use of water reducers can reduce water consumption and improve the working performance of UHPC while maintaining or increasing its strength. In addition, water reducers can improve the fluidity of UHPC, make the mix more uniform, help reduce pores and defects, and further improve the performance of UHPC.

[0041] (3) The slurry is then placed in a mold for shaping, and after 24 hours, the mold is removed for curing at a temperature of 20±2°C and a relative humidity of not less than 95%. The curing is continued for 28 days to obtain ultra-high performance concrete (UHPC).

[0042] The following performance tests were performed on the UHPC prepared above:

[0043] 1. Compressive strength test

[0044] The experiment used GB / T17671-1999 to test the compressive strength of the concrete specimens. The freshly mixed concrete slurry was poured into a 40mm×40mm×160mm rectangular mold. After hardening for 24 hours, the mold was removed and placed in a constant temperature curing room for curing. The compressive strength of the test block was measured at 3d, 7d and 28d. The test results are shown in the figure. Figure 1 shown.

[0045] 2. Shrinkage performance test

[0046] The experiment uses GB / T50082-2009 (2010) to test the autogenous shrinkage of UHPC. Freshly mixed concrete slurry is poured into the corrugated pipe, and the bubbles on the wall of the corrugated pipe are exhausted as much as possible. The two ends of the corrugated pipe are sealed with plastic plugs, and the displacement change of the corrugated pipe is continuously measured for 3 days using a contact sensor, which is the shrinkage of the concrete. The test results are as follows: Figure 2 shown.

[0047] 3. Impact resistance

[0048] The experiment used a high-altitude drop ball test to evaluate the impact resistance of different groups of concrete specimens. The concrete slurry was poured into a cylindrical mold with a diameter of 100 mm and a height of 50 mm. After hardening for 24 hours, the mold was removed and cured for 28 days. A 448 mm long steel pipe was used as the path of the cylindrical iron block. A 4.59 kg cylindrical iron block was vertically smashed on the small ball. Every 50 times, the changes in the UHPC test block were observed, and the energy conversion of the cylindrical iron block was calculated using the energy formula.

[0049] W=N×mgh

[0050] Where, W is the impact energy, J;

[0051] N——Number of impacts;

[0052] m——the mass of the impact hammer, 4.59kg;

[0053] g——gravitational acceleration of the impact hammer falling, 9.81m / s 2 ;

[0054] h is the height at which the impact hammer falls, 0.448m.

[0055] The impact results of the samples are shown in Table 2 and Figure 3 shown.

[0056] Example 2

[0057] This embodiment provides a method for preparing ultra-high performance concrete, which is different from embodiment 1 in that:

[0058] In step (1), 844 parts of pottery sand include 101 parts of pottery sand with a particle size of ≤0.6 mm, 345 parts of pottery sand with a particle size of 0.6-1.25 mm, 76 parts of pottery sand with a particle size of 1.25-2.36 mm, and 322 parts of pottery sand with a particle size of 2.36-4.75 mm; the remaining steps are the same.

[0059] In the performance test, the compressive strength test results are shown in Figure 1 , shrinkage performance test results refer to Figure 2 The impact resistance test results are shown in Table 2 and Figure 3 shown.

[0060] Comparative Example 1

[0061] This comparative example provides a method for preparing ultra-high performance concrete, which differs from implementation 1 in that: in step (1), all the pottery sand is replaced by an equal volume of river sand, and the specific river sand is calculated by weight, including 426 parts of river sand with a particle size of ≤0.6 mm, 417 parts of river sand with a particle size of 0.6-1.25 mm, and 479 parts of river sand with a particle size of 1.25-2.36 mm; the remaining steps are the same.

[0062] In the performance test, the compressive strength test results are shown in Figure 1 , shrinkage performance test results refer to Figure 2 The impact resistance test results are shown in Table 2 and Figure 3 shown.

[0063] Comparative Example 2

[0064] This comparative example provides a method for preparing ultra-high performance concrete, which differs from implementation 2 in that: in step (1), all the pottery sand is replaced by an equal volume of river sand, and the specific river sand is calculated by weight, including 158 parts of river sand with a particle size of ≤0.6 mm, 540 parts of river sand with a particle size of 0.6-1.25 mm, 119 parts of river sand with a particle size of 1.25-2.36 mm, and 504 parts of pottery sand with a particle size of 2.36-4.75 mm; the remaining steps are the same.

[0065] In the performance test, the compressive strength test results are shown in Figure 1 , shrinkage performance test results refer to Figure 2 The impact resistance test results are shown in Table 2 and Figure 3 shown.

[0066] For the convenience of comparison, the mass fractions of the materials in the embodiments and comparative examples are summarized in Table 1:

[0067] Table 1 Material composition of comparative examples and embodiments

[0068]

[0069]

[0070] Table 2 Calculation of impact energy

[0071]

[0072] Based on the above comparative examples and embodiments, the analysis is as follows:

[0073] Reference Figure 1 As shown in Table 1, Comparative Example 1, Comparative Example 2, Example 1 and Example 2 all showed excellent compressive strength, that is, the 28-day compressive strength was above 110 MPa, meeting the basic requirements of UHPC strength, indicating that the addition of coarse aggregate terracotta (particle size greater than 1.25 mm) does not affect the development of ultra-high performance concrete strength.

[0074] Depend on Figure 2 It can be seen that the shrinkage values ​​of Example 1 and Example 2 are significantly lower than those of Comparative Example 1 and Comparative Example 2, indicating that ceramic sand can significantly reduce the early shrinkage of ultra-high performance concrete. Figure 2 By comparing Example 1 with Example 2, it can be seen that Example 2, as the best example, adds large-particle-size (particle size greater than 2.36 mm) pottery sand on the basis of Example 1, adopts a combination of four particle sizes of ≤0.6 mm, 0.6-1.25 mm, 1.25-2.36 mm and 2.36-4.75 mm, and at the same time cooperates with the aforementioned pottery sand in different particle size ranges to achieve a tight stacking effect, lower early shrinkage of UHPC, achieve better shrinkage reduction effect, avoid cracking of UHPC, and extend its service life.

[0075] Referring to Table 2, the impact times of the first crack on the front and the energy required for the first crack to appear in Example 1 and Example 2 are significantly improved compared to the UHPC with fine aggregate (particle size less than 1.25mm) on the market (the impact times of the first crack are 3-50 times, and the corresponding energy required is 1000-1200J). In this application, ceramic sand is used as both coarse aggregate and fine aggregate, and the prepared UHPC exhibits more outstanding impact resistance. By comparing Example 1 and Example 2, it can be seen that Example 2, as the best example, adds large-particle-size (particle size 2.36-4.75mm) ceramic sand on the basis of Example 1, which can further improve the impact resistance of UHPC.

[0076] Referring to Table 2, it can be seen from the comparison between Comparative Example 1 and Example 1, or the comparison between Comparative Example 2 and Example 2 that the use of pottery sand as both coarse aggregate and fine aggregate has better impact resistance than using river sand as aggregate, and can also reduce the deadweight of UHPC. Figure 3 When the damage degree is similar, the corresponding "number of impacts" in Table 2 is combined with Figure 3 It can be seen that the impact resistance of the UHPC in Example 2 is the best.

[0077] Although the UHPC in Comparative Examples 1 and 2 and the UHPC in Examples 1 and 2 have different aggregate materials, they all use the same aggregate gradation. Although the impact resistance of the UHPC in Comparative Examples 1 and 2 is inferior to that of Examples 1 and 2, compared with the prior art (the energy required for the first crack is 1131.9 J), the UHPC in Comparative Examples 1 and 2 also show advantages, which indirectly reflects the advantages of the application of aggregate gradation in UHPC in the present application.

[0078] From the above experimental data of compressive strength, shrinkage and impact resistance, it can be concluded that the UHPC based on coarse aggregate ceramic sand provided by the present invention meets the UHPC compressive strength standard, while significantly reducing the shrinkage of UHPC, and most importantly, significantly improving the impact resistance of UHPC. It is used for buildings in earthquake-prone areas, offshore platform buildings, bridges and dams of water conservancy projects, and explosion-proof buildings, and exerts its excellent impact resistance.

[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An ultra-high performance concrete, characterized in that: The invention comprises, by weight: 700-800 parts of cement, 150-160 parts of silica fume, 210-220 parts of stone powder and 844 parts of pottery sand; Among them, there are 101-272 parts of pottery sand with a particle size of ≤0.6mm, 266-345 parts of pottery sand with a particle size of 0.6-1.25mm, 76-306 parts of pottery sand with a particle size of 1.25-2.36mm, and 0-322 parts of pottery sand with a particle size of 2.36-4.75mm.

2. The ultra-high performance concrete according to claim 1, characterized in that: The components include, by weight: 770 parts of cement, 150 parts of silica fume, 210 parts of stone powder and 844 parts of pottery sand; Among them, there are 270-272 parts of pottery sand with a particle size of ≤0.6mm, 266-268 parts of pottery sand with a particle size of 0.6-1.25mm, and 304-306 parts of pottery sand with a particle size of 1.25-2.36mm.

3. The ultra-high performance concrete according to claim 1, characterized in that: The components include, by weight: 770 parts of cement, 150 parts of silica fume, 210 parts of stone powder and 844 parts of pottery sand; Among them, there are 101-103 parts of pottery sand with a particle size of ≤0.6mm, 343-345 parts of pottery sand with a particle size of 0.6-1.25mm, 76-78 parts of pottery sand with a particle size of 1.25-2.36mm, and 320-322 parts of pottery sand with a particle size of 2.36-4.75mm.

4. The ultra-high performance concrete according to claim 1, characterized in that: The invention also comprises, by weight: 35-37 parts of polycarboxylate water-reducing agent and 200-220 parts of water.

5. The ultra-high performance concrete according to claim 4, characterized in that: 35 parts of polycarboxylate water reducer and 200 parts of water.

6. A method for preparing the ultra-high performance concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, first mix cement, silica fume and stone powder, then add pottery sand and mix well to obtain a mixed dry material; S2, adding the mixed water and water reducing agent to the mixed dry materials, stirring to form a slurry; S3, putting the slurry into a mold for shaping and curing to obtain the ultra-high performance concrete.

7. The preparation method according to claim 6, characterized in that: In S1, the stirring speed during the mixing process is 30-60 rpm, wherein cement, silica fume and stone powder are mixed for 30-40 s; The ceramic sand is added within 15 seconds, and then stirring is continued for 45-60 seconds to obtain a mixed dry material.

8. The preparation method according to claim 6, characterized in that: In S2, the stirring speed is 30-60 rpm, and after the mixed dry materials, water and water reducing agent are stirred to form a uniform slurry, the stirring is continued for 180 seconds to obtain the slurry.

9. The ultra-high performance concrete according to any one of claims 1 to 5, which is used for buildings in earthquake-prone areas, offshore platform buildings, bridges and dams of hydraulic engineering projects, and explosion-proof buildings.

Citation Information

Patent Citations

  • Green environment-friendly light-weight high-strength powder concrete

    CN103396064A

  • Ultra-high performance lightweight concrete taking pottery sand as lightweight aggregate and preparation method thereof

    CN112125603A

  • Ecological impact-resistant ultra-high performance concrete and application thereof

    CN113683361A